Antibody fingerprints in lyme disease deciphered with high density peptide arrays - Weber, Laura; Isse, Awale; Löffler, Felix (Engineering in life sciences, 2017)
Lyme disease is the most common tick-borne infectious disease in Europe and North America. Previous studies discovered the immunogenic role of a surface-exposed lipoprotein (VlsE) of Borreliella burgdorferi. We employed high density peptide arrays to investigate the antibody response to the VlsE protein in VlsE-positive patients by mapping the protein as overlapping peptides and subsequent in-depth epitope substitution analyses. These investigations led to the identification of antibody fingerprints represented by a number of key residues that are indispensable for the binding of the respective antibody. This approach allows us to compare the antibody specificities of different patients to the resolution of single amino acids. Our study revealed that the sera of VlsE-positive patients recognize different epitopes on the protein. Remarkably, in those cases where the same epitope is targeted, the antibody fingerprint is almost identical. Furthermore, we could correlate two fingerprints with human autoantigens and an Epstein-Barr virus epitope; yet, the link to autoimmune disorders seems unlikely and must be investigated in further studies. The other three fingerprints are much more specific for B. burgdorferi. Since antibody fingerprints of longer sequences have proven to be highly disease specific, our findings suggest that the fingerprints could function as diagnostic markers that can reduce false positive test results.
Gesehen am 28.03.2019